Understanding water consumption in a semi-permanent residential context through university student housing showers - Otrubina, Victoria V; Heydari, Zahra; Stillwell, Ashlynn S (Environmental research, infrastructure and sustainability : ERIS, 2025)
Understanding shower habits is critical for developing effective residential water conservation and efficiency strategies. Previous research has focused on single-family homes, but less is known about shower behavior among college-aged individuals in university student housing. This study examines the shower habits of students at the University of Illinois Urbana-Champaign, comparing them with U.S. single-family residential households regarding shower duration, time-of-day, and day-of-week. Using Conditional Tabular Generative Adversarial Networks to generate synthetic data, we address sample size limitations and confirm the validity of our results. Our findings reveal that student housing showers tend to be longer in duration and more variable compared to showers in single-family residences. Unlike the predictable routines seen in single-family homes, student housing inhabitants display less consistent showering habits, with different time-of-day patterns that challenge typical conservation incentives. Major shower events also occur more frequently before weekends in student housing. These insights emphasize the need for tailored water conservation strategies in semi-permanent residential settings. We recommend further exploration of targeted interventions, including educational campaigns, real-time feedback mechanisms, and gamification, to foster sustainable shower habits among university students. This study contributes to sustainable water management by providing actionable strategies within a sociotechnical systems lens for enhancing water conservation in semi-permanent residential contexts.